Constitutive Contribution by the Rice OsHKT1;4 Na+ Transporter to Xylem Sap Desalinization and Low Na+ Accumulation in Young Leaves Under Low as High External Na+ Conditions - Khan, Imran; Mohamed, Sonia; Regnault, Thomas; Mieulet, Delphine; Guiderdoni, Emmanuel; Sentenac, Hervé; Véry, Anne-Aliénor (Frontiers in Plant Science, 2020)
HKT Na+ transporters correspond to major salt tolerance QTLs in different plant species and are targets of great interest for breeders. In rice, the HKT family is composed of seven or eight functional genes depending on cultivars. Three rice HKT genes, OsHKT1;1, OsHKT1;4 and OsHKT1;5, are known to contribute to salt tolerance by reducing Na+ accumulation in shoots upon salt stress. Here, we further investigate the mechanisms by which OsHKT1;4 contributes to this process and extend this analysis to the role of this transporter in plants in presence of low Na+ concentrations. By analyzing transgenic rice plants expressing a GUS reporter gene construct, we observed that OsHKT1;4 is mainly expressed in xylem parenchyma in both roots and leaves. Using mutant lines expressing artificial microRNA that selectively reduced OsHKT1;4 expression, the involvement of OsHKT1;4 in retrieving Na+ from the xylem sap in the roots upon salt stress was evidenced. Since OsHKT1;4 was found to be also well expressed in the roots in absence of salt stress, we extended the analysis of its role when plants were subjected to non-toxic Na+ conditions (0.5 and 5 mM). Our finding that the transporter, expressed in Xenopus oocytes, displayed a relatively high affinity for Na+, just above 1 mM, provided first support to the hypothesis that OsHKT1;4 could have a physiological role at low Na+ concentrations. We observed that progressive desalinization of the xylem sap along its ascent to the leaf blades still occurred in plants grown at submillimolar Na+ concentration, and that OsHKT1;4 was involved in reducing xylem sap Na+ concentration in roots in these conditions too. Its contribution to tissue desalinization from roots to young mature leaf blades appeared to be rather similar in the whole range of explored external Na+ concentrations, from submillimolar to salt stress conditions. Our data therefore indicate that HKT transporters can be involved in controlling Na+ translocation from roots to shoots in a much wider range of Na+ concentrations than previously thought. This asks questions about the roles of such a transporter-mediated maintaining of tissue Na+ content gradients in non-toxic conditions.